Fractal antenna for rectenna system applications - Ismael, Mohammed Saadi (2020)
There are several challenges in developing an antenna for rectenna systems that are need to be addressed in such as low efficiency and large size of the antenna at the lower ISM frequency band. Hence, in this work a compact size and high efficiency antenna has been developed. As a result, a microstrip antenna structure based on a printed fractal patch geometry on an FR-4 epoxy substrate is proposed for radio frequency (RF) rectenna systems. The antenna circuitry is developed as triangular patch filled with conductive circles fed with a microstrip line and backed with a ground plane. Two matching circuit impedance are centred in the patch for enhancing the antenna bandwidth and tune the frequency modes. The proposed antenna performs two frequency modes at 920 MHz and 2.45 GHz to suite the rectenna system applications. A numerical simulation based on a Finite Integral Technique (FIT) of CST MWS formulations is conducted to study the antenna performance. The antenna is realized on FR-4 substrate with thickness of 1.6 mm. The measured return loss of 10 dB, gain of 4.47 dB, and efficiency of 92 % are achieved at these two bands. A compact size of (87.5 × 55) mm² is obtained. Finally, an omni-directional beam is obtained at 920 MHz and 2.45 GHz that would benefit the rectenna system applications.